COORDINATION OF VILLAGE COMMUNITY EMPOWERMENT INSTITUTIONS (LPMD) IN THE IMPLEMENTATION OF DEVELOPMENT IN BUTU VILLAGE, TILONGKABILA SUBDISTRICT BONE BOLANGO DISTRICT - Umar, Novel; Aneta, Asna (Universitas Negeri Gorontalo, 2022)
The purpose of this study is to describe how the coordination of the Village Community Empowerment Institution (LPMD) in the implementation of development in Butu Village, Tilongkabila District, Bone Bolango Regency. The research method is descriptive with a qualitative approach. The results of the study indicate that the vertical coordination in Butu Village has not been maximized, this can be seen by the absence of togetherness between all parties in the institution, so that the problems that arise cannot be overcome together. Horizontal coordination between institutions in the village can be said to have not gone well, this can be seen from the lack of cooperation between the LPMD management and other institutions, so that planning and decision-making related to village development does not involve LPMD. LPMD is a partner of the Village government, it should know the duties and functions of each administrator. Every important decision making related to development in an area can be well coordinated between the village government and other institutions. The coordination carried out by the LPMD can assist the village government in implementing village development programs, but this has not gone well, because the Butu LPMD has not played an active role in the activities carried out by Butu Village.